2021
DOI: 10.1021/acs.jced.1c00220
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2-Butanol Addition on Waste Cooking Oil Biodiesel Density: An Updated Experimental Measurement and Thermodynamic Modeling Study

Abstract: Biodiesels will become the most popular alternative energy resource to fossil diesels; they can be used alone or blended with an oxygenated additive in any proportion. The properties of biodiesels strongly depend on the type of the fatty acid methyl esters (FAME) that compose them. The main objective of the present work is to investigate the influence of 2-butanol addition on the waste cooking oil biodiesel (WCOB), for this fact, the new experimental density data (952 points) of WCOB + 2-butanol binary mixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In fact, interactions in 2-butanol-based systems have been only partially investigated by a computational approach, mainly through density functional theory (DFT) calculations, focusing on chirality aspects , or on clathrate structure formation . The interest in studying 2-butanol relies mainly in its uses in the fuel industry, both as an additive , and as a platform for biofuel production. , Further fields of application regard the food industry, , electrosorption, , and hydrogenation routes …”
Section: Introductionmentioning
confidence: 99%
“…In fact, interactions in 2-butanol-based systems have been only partially investigated by a computational approach, mainly through density functional theory (DFT) calculations, focusing on chirality aspects , or on clathrate structure formation . The interest in studying 2-butanol relies mainly in its uses in the fuel industry, both as an additive , and as a platform for biofuel production. , Further fields of application regard the food industry, , electrosorption, , and hydrogenation routes …”
Section: Introductionmentioning
confidence: 99%
“…From Table , it can be concluded that the blends involving ethanol were the most studied up to 2015 and that next higher alcohols occupied the research. Prior to now, only Aitbelale et al determined density in wide ranges of temperature and pressure for 2-butanol + biodiesel. They used Tait and PC-SAFT equations of states to model density as a function of temperature and pressure.…”
Section: Introductionmentioning
confidence: 99%
“…At 298.15 K and 0.1 MPa, the average (6.80 ± 0.10) MPa −1 was reported for the Tait equation was used in this work to model the density of all the studied systems. From the particular form of Tait EoS, eq 20, which was used to correlate the density of all the mixtures biodiesel (1) + isobutanol (2), the following equation is obtained 29) In Figure 15, the relative deviations in k T between the values from eq 29 and those from eq 28 are represented for the blends as a function of pressure for some isotherms. It can be concluded that the Tait equation allows for a good representation of both density (AARD % = 0.035%, see Table 11) and k T (with AARD % = 0.6%) in the studied temperature, pressure, and isobutanol mass fraction ranges.…”
mentioning
confidence: 99%